Сhildfree in the Focus of Qualitative Sociological Research - Oleksandr Zubariev (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Соціологічні дослідження сучасного суспільства: методологія, теорія, методи, 2021)
The article deals with the problematics of childfree in sociological discourse. It is noted that the concept of "childfree" appears in the context of rethinking the prevailing public discourse about childlessness. If the concept of “childless” refers to people who are childless for reasons beyond their control, then the concept of “childfree” refers to people who are childless because they themselves made such a choice. Attention is focused on the insufficient development of this issue in modern Ukrainian sociology. A review of sociological studies of the childfree phenomenon, implemented using qualitative methods, is carried out. In particular, the work of the British sociologist Josephine Davies, devoted to the question of how women who choose not to be mothers experience the period from 45 to 55; the study by J. Veevers, who singles out "early articulators", "postponers", "aficionados" and "rejectors" among the childfree; E. Campbell, who shows that sometimes the nature of the relationship between a woman and her mother can influence a woman's choice to be a childfree in the future; R. Gillespie, who studies in detail the formation of the identity of chіldfree women; P. Bonnici, who studies the impact of voluntary childlessness on a woman's identity; K. Park, which reveals the strategies of stigma management that use childfree; A. Campbell, who studies the social perception of women who have chosen sterilization as a permanent form of contraception. The opinion is expressed that the phenomenon of childfree can be considered in the context of "aesthetics of existence" or "self-technique" (M. Foucault), because the question of whether or not to have children is not subject to strict moral prohibitions, but rather intense moral issues. If voluntary childlessness is a form of stylization of life, then, accordingly, it can be analyzed in such aspects as: determination of ethical substance, way of self-subordination, form of ethical work and teleology of the moral subject.